Post-challenge insulin concentration is useful for differentiating between coronary artery disease and cardiac syndrome X in subjects without known diabetes mellitus. Issue 1 (December 2017) - Liang, Kae-Woei; Sheu, Wayne; Lee, Wen-Jane; Lee, Wen-Lieng; Pan, Hung-Chih; Lee, I.-Te; Wang, Jun-Sing
Abstract Background Cardiac syndrome X (CSX) is characterized by angina pectoris but with patent coronary arteries. Our previous study demonstrated that subjects with CSX had a higher fasting insulin-resistance (IR) than the controls. However, few studies have investigated the degree of IR, including oral glucose tolerance test (OGTT)-derived indices and profiles of metabolic abnormalities between CSX and coronary artery disease (CAD). Methods Ninety-two CSX and 145 CAD subjects without known diabetes mellitus (DM) underwent coronary angiogram (CAG) for angina pectoris and also agreed to receive OGTT and glycated hemoglobin (HbA1C ) evaluations for screening abnormal glucose regulation and IR. Results CAD group had more subjects with metabolically unhealthy obesity (52.4 vs. 31.5%, p < 0.001) than the CSX group. The CAD group had higher OGTT 2 h glucose and insulin (both p < 0.005) while fasting glucose, insulin and HOMA-IR were similar to those of CSX subjects. In the binary regression analysis, OGTT 2 h insulin and being metabolic unhealthy were significantly different between the CAD and CSX groups, but there were no significant differences in Matsuda index, fasting glucose, insulin, HOMA-IR, or HbA1C . Conclusions Post challenge OGTT 2 h insulin and being metabolic unhealthy were useful parameters in differentiating between CAD and CSX in subjects without known DM but suffered from angina pectoris and underwent CAG. Different degrees of IR and metabolic abnormalities might be implicated in the pathogenesis of micro vs. macro vascular coronary diseases. Trial registration NCT01198730 athttps://clinicaltrials.gov, Registered Sep. 8, 2010